2019
DOI: 10.1063/10.0000132
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structures and nanoscale electronic states on the surface of MgB2 superconductor observed by scanning tunneling microscopy and spectroscopy

Abstract: The systematic study of the nanoscale local electronic states on the MgB2 surface was performed using the low-temperature scanning tunnel microscopy/spectroscopy (STM/STS). The STM topography shows the atomic image of the hexagonal lattice with the constant parameter a’ = 0.31 nm, which is identified as mainly the Mg site occupancy. The temperature-dependent STS measurements were analyzed assuming the existence of two energy gaps. As a result, the fitting gap amplitudes Δfit ≃ 10.2 meV and 4.8 meV were found a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…We acknowledge the possibility that ball milling could enhance the kinetics of surface disordering within our samples. However, Sugimoto et al 26 similarly observed through scanning tunneling microscopy that boron atoms on a freshly cleaved MgB 2 sheets are randomly distributed and irregularly arranged even in the absence of ball milling. These results confirm that surface disordering also occurs under nonaggressive synthetic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We acknowledge the possibility that ball milling could enhance the kinetics of surface disordering within our samples. However, Sugimoto et al 26 similarly observed through scanning tunneling microscopy that boron atoms on a freshly cleaved MgB 2 sheets are randomly distributed and irregularly arranged even in the absence of ball milling. These results confirm that surface disordering also occurs under nonaggressive synthetic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Li et al 25 confirmed a loss of oxidized borate signal from X-ray photoemission spectroscopy of FeB 2 following surface hydrogen evolution, suggesting Fe surfaces are leached by the electrolyte under reaction conditions to expose the boron surface underneath. Another recent study by Sugimoto et al 26 confirmed boron-rich surfaces of freshly cleaved MgB 2 sheets using low-temperature surface-sensitive scanning tunneling microscopy. Under such conditions, however, surface structure cannot be straightforwardly assessed.…”
Section: Introductionmentioning
confidence: 95%
“…Having at hand such samples, we were able to obtain surface atomic images and the electronic structures because our STM equipment possesses a XY movement mechanism with an optical microscope system capable to seek for suitable surfaces. The STM/STS apparatus used in this study is the commercially based system (Omicron LT-STM) with above-mentioned XY movement mechanism and upgrading modifications [45][46][47][48]. The crystals were cleaved at 77 K under the ultra-high vacuum atmosphere of ∼10 −8 Pa.…”
Section: Methodsmentioning
confidence: 99%
“…Actually, the STS measurements of Ni-doped cuprate Bi-based superconductors clarified that they possess d-wave order parameters [8]. In addition, we have previously carried out the STS measurements of the local quasiparticle density of states (LDOS) distributions in MgB 2 and found the spot structures of the zero-bias peak being due to certain impurities [9] and the LDOS spots of multi-layered apical F cuprate superconductors due to the irregularities of apical O/F ratios [10][11][12][13]. On the other hand, in the case of iron superconductors, the impurity signal at the atomic scale was widely observed as the spot structures created by the excess Fe in pristine FeTe [14], various shapes of spot structures with multiple peaks in iron 111-type LiFeAs [15], and unidirectional LDOS structures in 122 type CaFe 2 As 2 samples demonstrating the nematic order [16].…”
Section: Introductionmentioning
confidence: 99%